Queer Sewing as a Way of Life: resistances to neoconservatisms of race and gender - Miranda, Shirley Aparecida de; Silva, Jaime Peixoto da (Revista Brasileira de Estudos da Presença, 2024)
ABSTRACT This article brings out strategies for confronting neoconservatisms of gender and race through what is here called queer sewing. Based on the narrative patches produced in doctoral research, the relationship between clothes and the norm is discussed. The concepts of ancestry and intersectionality are mobilized to problematize the remodeling of the self in the confrontation with cisheteronorm and normative whiteness. It was noticed that queer sewing can be seen as a strategic way of life, as it highlights a certain work on oneself on the part of the subject that speaks of an ethical way of existing in the world, a process in which not only clothes were pro-duced, but, mainly, a form of existence. RESUMO Este artigo evidencia estratégias de enfrentamento aos neoconservadorismos de gênero e raça por meio do que aqui é nomeado costura queer. Com base nos retalhos narrativos produzidos em pesquisa de doutorado, discute-se a relação entre as roupas e a norma. Mobilizam-se os conceitos de ancestralidade e de interseccionalidade, para problematizar a remodelagem de si no confronto com a cis-heteronorma e a bran-quitude normativa. Percebeu-se que a costura queer pode ser vista como um modo estratégico de vida, ao evidenciar certo trabalho sobre si mesmo por parte do sujeito que diz de um modo ético de existir no mun-do, um processo no qual não só roupas foram produzidas, mas, principalmente, uma forma de existência RÉSUMÉ Cet article met en lumière des stratégies pour affronterles néoconservatismes de genre et de race à travers ce que l’on appelle ici la couture queer. À partir des fragments narratifs produits lors de la recherche doctorale, la relation entre le vêtement et la norme est discutée. Les concepts d’ascendance et d’intersectionnalité sont mobilisés pour problématiser le remodelage de soi dans la confrontation avec la cisheteronorm et la blan-cheur normative. Il a été remarqué que la couture queer peut être considérée comme un mode de vie straté-gique, car elle met en évidence un certain travail sur soi de la part du sujet qui parle d'une manière éthique d’exister dans le monde, un processus dans lequel non seulement les vêtements sont produit, mais surtout une forme d’existence.